2015
DOI: 10.1007/s11912-015-0451-3
|View full text |Cite
|
Sign up to set email alerts
|

Tivozanib: Status of Development

Abstract: Tivozanib is a potent and highly specific orally available, tyrosine kinase inhibitor that targets vascular endothelial growth factor (VEGF) receptor-1, VEGF receptor-2, and VEGF receptor-3 at very low concentrations with a long half-life (4 days). After its promising activity in xenograft and preclinical models, tivozanib was evaluated in early phase clinical trials in various solid tumors. The phase III trial (TIVO-1) compared tivozanib with sorafenib in metastatic clear cell renal cell carcinoma (RCC). Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…9,10 Additionally, antitumor efficacy of tivozanib has been evaluated in solid tumors such as gastrointestinal cancers and breast cancer. 8,10 Safety and tolerability profiles of tivozanib have been shown to be acceptable when used in combination therapy. 11 c-Kit signaling promotes cell proliferation and survival and this pathway has been shown to be aberrantly activated in cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Additionally, antitumor efficacy of tivozanib has been evaluated in solid tumors such as gastrointestinal cancers and breast cancer. 8,10 Safety and tolerability profiles of tivozanib have been shown to be acceptable when used in combination therapy. 11 c-Kit signaling promotes cell proliferation and survival and this pathway has been shown to be aberrantly activated in cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Tivozanib specific progression-free survival in metastatic colorectal patients was associated with low-serum neuropilin-1 (NRP-1) levels and NRP-1 seemed to be a biomarker of tivozanib response in clinical trials. 9 , 10 Additionally, antitumor efficacy of tivozanib has been evaluated in solid tumors such as gastrointestinal cancers and breast cancer. 8 , 10 Safety and tolerability profiles of tivozanib have been shown to be acceptable when used in combination therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the lipophilic diaryl urea moiety served as a key structural fragment for binding with the hydrophobic pocket of the kinase domain through hydrogen bonds and hydrophobic interactions [5]. Subsequently, diverse diaryl urea derivatives were developed successively in the past decades, such as linifanib [6], tivozanib [7], and ki8751 [8] (Figure 1). Therein, thieno[3,2- d ]pyrimidine derivative S1 bearing diaryl urea moieties at the C-2 positon exhibited significant inhibition of tyrosine kinases, including c-Kit, orphan receptor tyrosine kinase (RET), and FLT3 for its prominent framework [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two of these molecules (crizotinib and GSK-1120212) are known kinase inhibitors of hROS1 and pathway components. The third molecule (AV-951 12 ) was active specifically against hROS1 but not mFGFR1 or hEGFR ( Supplementary Fig. 10).…”
mentioning
confidence: 99%